2011
DOI: 10.4028/www.scientific.net/amr.383-390.3320
|View full text |Cite
|
Sign up to set email alerts
|

Deep Cryogenic Treatment on Aluminum Silicon Carbide (Al-SiC) Composite

Abstract: Deep cryogenic treatment produces a significant enhancement in the mechanical properties of metals. In this research paper, the mechanical properties of Aluminium Silicon composite were studied when they were subjected to deep cryogenic treatment. Samples were prepared from two different compositions of Aluminum silicon composites (Al 2024_5%SiC & 10%SiC). The samples were given controlled cryogenic treatment at -186oC. Treated samples were compared with un-treated samples for their compressive strength, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Rasool et al [12] examined the DCT of Al-SiC Composite. They reported that the treated specimens haddemonstrated an enhanced compressive strength.…”
Section: Iintroductionmentioning
confidence: 99%
“…Rasool et al [12] examined the DCT of Al-SiC Composite. They reported that the treated specimens haddemonstrated an enhanced compressive strength.…”
Section: Iintroductionmentioning
confidence: 99%